Topical isotretinoin for melasma in Thai patients: A vehicle-controlled clinical trial - Vichit Leenutaphong (2018)
Background: Melasma is an acquired hyperpigmentary disorder commonly seen in Orientals. Recently it has been demonstrated that tretinoin (all- trans-retinoic acid) can produce significant clinical improvement of melasma. However, moderate cutaneous side effects (retinoid dermatitis) occurred in a number of patients. Objective: To investigate the efficacy of topical 0.05 per cent isotretinoin gel (Isotrex) in the treatment of melasma in Thai patients. Method: Thirty patients with moderate to severe melasma entered a 40-week, randomized, vehicle-controlled clinical trial in which they applied either 0.05 per cent isotretinoin gel, or its vehicle base together with a broad spectrum sunscreen (SPF 28) daily to the entire face. They were evaluated clinically (using Melasma Area and Severity Index), and colorimetrically (using our Melasma Area and Melanin Index). Results: After 40 weeks, the average MASI and MAMI scores of the isotretinoin-treated group decreased by 68.2 per cent and 47 per cent respectively, while the corresponding control scores declined 60 per cent and 34 per cent. There was no statistically significant difference between the isotretinoin and vehicle groups. When the MASI and MAMI scores of each visit were compared to their baseline data, a statistically significant reduction of the score was first noted at weeks 4 and 12 respectively. Lightening of melasma, as determined clinically (MASI score), correlated well with pigmentation measurements (MAMI score). Side effects were limited to a mild transient 'retinoid dermatitis' occurring in 27 per cent of isotretinoin-treated patients. Conclusion: Daily use of broad spectrum sunscreen has a significant lightening effect on melasma in Thai patients. However, there was no statistically significant difference between the isotretinoin and vehicle-treated group.